Upregulation of Slug expression by cyclosporine A contributes to the pathogenesis of gingival overgrowth - Chung-Hung Tsai; Cheng-Chia Yu; Shiuan-Shinn Lee; Hui-Chieh Yu; Fu-Mei Huang; Yu-Chao Chang (Journal of the Formosan Medical Association, 2016)
Gingival overgrowth occurs as a side effect of systemic medication with immunosuppressant cyclosporine A (CsA). Slug, a master regulator of epithelial–mesenchymal transition, is dramatically upregulated in a variety of fibrotic diseases. The aim of this study is to investigate the role of epithelial–mesenchymal transition marker Slug in the pathogenesis of CsA-induced gingival overgrowth. Methods: Clinically healthy gingiva and CsA-induced gingival overgrowth specimens were analyzed by immunohistochemistry. The effect of CsA on normal human gingival fibroblasts (HGFs) was used to elucidate whether Slug expression could be affected by CsA by real-time reverse transcription-polymerase chain reaction and western blot. Cell proliferation in CsA-treated HGFs with Slug lentiviral-mediated shRNAi knockdown was evaluated by tetrazolium bromide reduction assay. Results: Slug expression was higher in CsA-induced gingival overgrowth specimens than in clinical healthy gingiva (p < 0.05). Slug expression was significantly higher in CsA-induced gingival overgrowth specimens with higher levels of inflammatory infiltrates (p < 0.05). CsA was found to increase Slug transcript and protein expression in HGFs in a dose-dependent manner (p < 0.05). In addition, knockdown of Slug significantly suppressed CsA-induced cell proliferation in HGFs (p < 0.05). Conclusion: Taken together, upregulation of Slug in HGFs stimulated by CsA may play an important role in the pathogenesis of CsA-induced gingival overgrowth.